ANALISIS FATWA DSN-MUI NOMOR: 4/DSN-MUI/IV/2000 TENTANG AKAD MURABAHAH DALAM PENERAPAN HAK MILIK - Andi Asruni; Zainal Said; Damirah (Institut Agama Islam Negeri Parepare, 2022)
Bank Muamalat KCP Parepare is one of the Islamic banks whose operational activities implement a murabahah financing system. Regarding murabahah itself, it is clearly regulated in the DSN MUI fatwa No: 04/DSN-MUI/2000, concerning murabahah which states that